2001
DOI: 10.1385/bter:82:1-3:029
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Erythrocyte Lipid Peroxide Levels in Workers with Occupational Exposure to Lead

Abstract: The plasma and erythrocyte lipid peroxide levels were measured in a group of male subjects occupationally exposed to lead for an average period of 17 yr, and compared to those from an age-matched control group living in the same city in a similar socioeconomical environment. The blood lead and plasma zinc levels were measured by atomic absorption spectroscopy. The plasma and erythrocyte lipid peroxide levels were established by the malondialdehyde determination method. Significant differences were found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…In agreement with a previous study, 18 Pb level was associated with duration of Pb exposure. Interestingly, duration of Pb exposure was also correlated with CAT, α‐tocopherol, β‐carotene and MDA in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with a previous study, 18 Pb level was associated with duration of Pb exposure. Interestingly, duration of Pb exposure was also correlated with CAT, α‐tocopherol, β‐carotene and MDA in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Significant association between MDA and indices of OS confirms the role of OS on the generation of LPO in erythrocytes of apprentices. The association between Pb and MDA supports Pb as the primary factor causing LPO and also, in agreement with recent studies, suggests this event as a possible mechanism for some of Pb’s toxic effects 17–22 …”
Section: Discussionsupporting
confidence: 88%
“…There was observed significantly higher plasma MDA levels (2.67 ± 0.69 μM) of workers exposed to lead than those in the control group (1.23 ± 0.61 μM) [51]. However, the results presented by Dursun et al indicate that increased concentrations of lipid peroxidation products in the blood of persons exposed to lead is dependent not only on the concentrations of lead, but also on the age and time of exposure [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results presented by Dursun et al indicate that increased concentrations of lipid peroxidation products in the blood of persons exposed to lead is dependent not only on the concentrations of lead, but also on the age and time of exposure [51]. Other researches have also shown that MDA concentrations were elevated in the all heavy metal-treated groups compared to the control groups [52].…”
Section: Discussionmentioning
confidence: 99%
“…Lead induces oxidative stress to the brain, heart, kidney and reproductive organs by affecting membranes, DNA and antioxidant defence systems of cells ( 1 ) . Aside from lipid peroxidation reactions evidenced by elevations in malondialdehyde, lead appears to enhance oxidative damage to DNA as shown by an increase of 8-hydroxydeoxyguanosine (8-OHdG) ( 2 4 ) . In epidemiological studies, blood lead levels (BLL) have been reported to have adverse health impacts such as oxidative stress, mortality and raised homocysteine levels ( 5 7 ) .…”
mentioning
confidence: 99%